Pengaruh Substitusi Tepung Ubi Ungu pada Pembuatan Kue Kastengel Terhadap Kualitas Organoleptik dan Tingkat Kesukaan - Diah Dwi Wahyuni; Ambar Rukmini; Anggri Sekar Sari (AGROTECH : JURNAL ILMIAH TEKNOLOGI PERTANIAN, 2025)
This study aims to determine 1) the effect of purple sweet potato flour substitution with a percentage of 10%, 20%, and 30% on the organoleptic quality of kastengel in terms of aroma, color, taste, and texture 2) the level of public preference for the quality of kastengel with 10%, 20%, and 30% purple sweet potato flour substitution in terms of aroma, color, taste, and texture. The questions in the study were: 1) is there an effect of purple sweet potato flour substitution with a percentage of 10%, 20%, and 30% on the organoleptic quality of kastengel cakes in terms of aroma, color, taste, and texture? 2) what is the level of public preference for kastengel cakes with 10%, 20%, and 30% purple sweet potato flour substitution in terms of aroma, color, taste and texture? This research uses pure experiment with RAL. Sampling technique with simple random sampling method. Conducted in Minggiran Village, the research subjects were 15 semi-trained panelists and 60 untrained panelists. The data collection method used observation of the organoleptic test. The research instrument was a questionnaire, a rating scale for the differentiation test with a score of 1 - 5, while a scale of 1 - 4 for the liking test. Data analysis techniques using ANOVA, with a confidence level of 95%, if significantly different, followed by LSD test. The results of this study showed that: 1) there is an effect of purple sweet potato flour substitution on the quality of 10%, 20%, and 30% kastengel. The best quality of kastengel is purple sweet potato flour substitution of 20%.